2020
DOI: 10.1155/2020/6716908
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Gene Signature to Predict Overall Survival in Head and Neck Squamous Cell Carcinoma

Abstract: Background. Head and neck squamous cell carcinoma (HNSCC) is a common malignancy that emanates from the lips, mouth, paranasal sinuses, oropharynx, larynx, nasopharynx, and from other pharyngeal cancers. The availability of high-throughput expression data has made it possible to use global gene expression data to analyze the relationship between metabolic-related gene expression and clinical outcomes in HNSCC patients. Method. In this study, we used RNA sequencing (RNA-seq) data from the cancer genome atlas (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSCC) refers to an epithelial malignant tumor that originates in the head and neck and over 600,000 new cases are reported every year (1,2). Although advances in technology and supportive treatment have improved the quality of life of HNSCC patients, the overall prognosis is still poor due to local recurrence and distant metastasis after surgery (3,4). Therefore, there is an urgent need to better understand the molecular mechanism of HNSCC progression to improve the prevention, diagnosis, and personalized treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) refers to an epithelial malignant tumor that originates in the head and neck and over 600,000 new cases are reported every year (1,2). Although advances in technology and supportive treatment have improved the quality of life of HNSCC patients, the overall prognosis is still poor due to local recurrence and distant metastasis after surgery (3,4). Therefore, there is an urgent need to better understand the molecular mechanism of HNSCC progression to improve the prevention, diagnosis, and personalized treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, great progress has been made in the research and treatment of LSCC [13,14]. However, treatment resistance increases the recurrence rate of LSCC and patients who undergo total laryngectomy have a poor quality of life [15]. This study screened the differentially expressed genes to provide ideas for subsequent studies, including the exploration of potential diagnostic targets, which is conducive to the risk assessment of LSCC at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…As the sixth most common cancer, head and neck squamous cell carcinoma (HNSCC) is a malignancy of head and neck origin ( Galizia et al, 2022 ). Wu et al screened HNSCC patients for differentially expressed RNA based on the TCGA database and found that patients with HNSCC with low CHDH expression had the best prognosis using univariate Cox regression models ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%